Attitudes towards Mobile Advertising – A Research to Determine the Differences between the Attitudes of Youth and Adults in Malaysia - Zhang, Shan (2014)
As wireless technology develops, the rapid explosion of mobile phones along with the technological development has created a whole new marketing medium named mobile advertising. It is the most widely adopted to promote the products or services by the marketers. As more popular start using this channel, there is a business in competition. In the face of competition, the advertisers want to attract more users and increase their market share. However, in order to do this, advertisers need to build a good relationship with consumers which can attract consumers accept mobile advertising via their mobile phones, which is the key factor to achieve the market share. This study aims to investigate the factors influencing Malaysian customers’ attitudes towards mobile advertising. The significance of this study is to better understand the customer demand and to allow opportunity for mobile advertisers to create better ways in view of offering better services to customers. This research uses the descriptive research design and a primary method of data collection. In addition, SPSS 20 is used to analyze the data. SPSS was used to analyze the descriptive demographic and test the relationship of the constructs.